'SEKOLAH SEHAT': SOSIALISASI TENTANG PERILAKU HIDUP BERSIH DAN SEHAT DI SEKOLAH - Suskha, Fadhila; Sugiarta, Chalik; Lara Octavia, Angel; Rara Putri, Mentari; Rosdiyanti, Dian; Ayu Wulandari, Felisa (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2024)
‘Healthy Schools’: Socialization of clean and healthy living behaviors in schools is an important initiative in shaping an educational environment that supports student health. The program aims to instill the values of health and hygiene early on, so that students can develop sustainable healthy living habits. In its implementation, the program is faced with various challenges, ranging from collaboration between schools, parents, and communities, to creativity in delivering PHBS messages to students. With strong collaboration, creativity in program implementation, as well as increased awareness and commitment from all relevant parties, it is hoped that the “Healthy School” program can have a positive impact in shaping a healthy, smart and quality young generation. This abstract will discuss the importance of socializing clean and healthy living behaviors in schools and provide practical guidance in running the “Healthy School” program effectively and sustainably.